Past, present and future research on the one-humped camel in Africa. A review - Wilson, R.T.; Bourzat, D. (1988)
Briefly reviews the importance of the one-humped camel in Africa. Looks at past research based on 3000 literature items and major aspects of research currently being undertaken in Africa. Presents proposals for future research that will be cost effective and relevant to improving the productivity of the camel.